SMART FINANCIAL MAPPING: COMMUNITY MENTORING FOR DIGITAL BOOKKEEPING IN MICRO ENTERPRISES - Nova Krisnawati; Siti Zuhroh; Sa'diyah Sa'diyah (Community Development Journal : Jurnal Pengabdian Masyarakat, 2025)
Micro enterprises play a vital role in Indonesia’s economic ecosystem, yet many continue to face serious challenges in managing their financial records due to low digital literacy and the absence of structured bookkeeping systems. This community service program, titled Smart Financial Mapping: Community Mentoring for Digital Bookkeeping in Micro Enterprises, aimed to empower micro business actors in Kelurahan Margodadi, Metro Selatan, through participatory mentoring focused on digital financial management. Using the Participatory Action Research (PAR) approach, the program was conducted over three months and involved training, mentoring, and monitoring activities using the BukuWarung mobile application. Data collection techniques included surveys, interviews, observations, and focus group discussions, while analysis combined quantitative statistical testing and thematic qualitative analysis. The results showed a significant improvement in financial literacy and digital bookkeeping practices, with increased confidence and behavioral change among participants. Despite some limitations related to digital access and literacy gaps, the mentoring approach proved effective in fostering long-term financial awareness. This program contributes to the development of inclusive digital transformation strategies for micro enterprises and highlights the value of sustained, community-based mentoring in achieving financial resilience.